Minions - Coffin, Pierre; Balda, Kyle; Meledandri, Chris; Healy, Janet; Lynch, Brian (Brian Michael), 1973-; Bullock, Sandra; Hamm, Jon, 1971-; Keaton, Michael, 1951-; Janney, Allison; Coogan, Steve; Saunders, Jennifer; Rush, Geoffrey, 1951-; et al. (Universal City, CA : Universal Studios Home Entertainment, 2015)
When Minions Kevin, Stuart and Bob set out to find the Minions a new villain to serve, they find much more than they bargained for.
Videodisc release of the 2015 animated motion picture.
Originally part of a Blu-ray + DVD Combo pack. 025192188701
Bonus features on DVD include the mini-movies Crominion, Competition, and, around the world interactive map, Binky Nelson unpacified, a deleted scene, and the featurette Jingle bells Minion style.
Editor, Claire Dodgson ; score, Heitor Pereira.
Voices: Sandra Bullock, Jon Hamm, Michael Keaton, Allison Janney, Steve Coogan, Jennifer Saunders, Pierre Coffin, Geoffrey Rush.
MPAA rating: PG; for action and rude humor.
Keywords: Supervillains -- Drama; Good and evil -- Drama; Good and evil -- Drama; Supervillains -- Drama; Children's films; Animated films; Comedy films; Fiction films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities